Assessment of branched GDGTs as temperature proxies in sedimentary records from several small lakes in southwestern Greenland. (May 2015) - Colcord, Devon E.; Cadieux, Sarah B.; Brassell, Simon C.; Castañeda, Isla S.; Pratt, Lisa M.; White, Jeffrey R.
Highlights: The 5 lake environments vary in physical and chemical properties. Br GDGTs in sediment cores, surface sediments and local soils were examined. Lakes exhibited differences in br GDGT distributions despite their close proximity. Br GDGT-based temperature in low O2 lakes correlated with bottom water temperature. Br GDGT distributions in lake sediments suggest an in situ anaerobic source. Abstract: This study of five small (<3.0 ha) lakes in southwestern Greenland examines the veracity of branched glycerol dialkyl glycerol tetraethers (br GDGTs) as a temperature proxy in lacustrine systems. The proximity (<5 km) of the lakes suggests that their temperature history, and thus their br GDGT records, should be similar. Distributions of br GDGTs in (i) surface sediments from all five lakes, (ii) 14 C-dated sediment cores from two lakes (Upper and Lower EVV Lakes) and (iii) soil samples from the area surrounding the lakes were examined. The temporal records of br GDGT-based temperature for the two cores exhibited both similarities and major discrepancies. The differences between the paleotemperature records for the two lakes suggest that br GDGTs are not solely soil-derived, reflecting air temperature, but also indicate an additional br GDGT contribution from another source. Among the broader suite of lake sediments, there was a strong correlation ( R 2 0.987) between br GDGT-based surface sediment temperatures and measured summer bottom water temperatures for the four lakes with hypoxic/anoxic bottom waters, including Upper EVV Lake. The correlation suggests production of br GDGTs by anaerobic bacteria within the bottom water and/or sediment–water interface, reflecting environmental temperature for the individual lakes and augmenting the uniform, soil-derived signal. Hence, assessment of br GDGTs in Greenland lake sediments provides evidence for their origin from anaerobic autochthonous bacteria and indicates that interpretation of lacustrine br GDGT-based paleotemperature records requires contextual knowledge of individual lake systems and potential source(s) of sedimentary br GDGTs.